2022
DOI: 10.1158/1535-7163.mct-21-0554
|View full text |Cite
|
Sign up to set email alerts
|

DS-7300a, a DNA Topoisomerase I Inhibitor, DXd-Based Antibody–Drug Conjugate Targeting B7-H3, Exerts Potent Antitumor Activities in Preclinical Models

Abstract: B7-H3 is overexpressed in various solid tumors and has been considered as an attractive target for cancer therapy. Here, we report the development of DS-7300a, a novel B7-H3–targeting antibody–drug conjugate with a potent DNA topoisomerase I inhibitor, and its in vitro profile, pharmacokinetic profiles, safety profiles, and in vivo antitumor activities in nonclinical species. The target specificity and species cross-reactivity of DS-7300a were assessed. Its pharmacologic activities were evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…6B). We confirmed that B7-H3 is expressed in the majority of prostate cancers, consistent with what has been previously described ( 32 , 33 ), and its expression ranges from low to high regardless of disease state (Fig. 6, B and C), with higher expression of B7-H3 being associated with inferior survival in patients with CRPC-Adeno ( P = 0.0206) (fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6B). We confirmed that B7-H3 is expressed in the majority of prostate cancers, consistent with what has been previously described ( 32 , 33 ), and its expression ranges from low to high regardless of disease state (Fig. 6, B and C), with higher expression of B7-H3 being associated with inferior survival in patients with CRPC-Adeno ( P = 0.0206) (fig.…”
Section: Resultssupporting
confidence: 91%
“…DS-7300a is composed of a humanized anti–B7-H3 monoclonal antibody, an enzymatically cleavable linker, and a potent DNA topoisomerase 1 inhibitor (DXd). The payload agent, DXd, causes apoptosis of cancer cells that express B7-H3 on their cell surface ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of these is sacituzumab govitecan (Trodelvy ® ), an anti-TROP-2 IgG1 antibody conjugated to SN-38, and the other is trastuzumab deruxtecan (Enhertu ® ), an anti-HER2 IgG1 antibody conjugated to deruxtecan (Dxd). SN-38 and Dxd are both related to the plant alkaloid camptothecin, and inhibit topoisomerase enzymes essential for the relaxation of supercoils during DNA replication, with Dxd being a higher-potency analogue of SN-38 [ 35 , 36 , 37 ]. Inhibition of topoisomerase function leads to DNA strand breaks during replication, followed by cell death through apoptosis [ 36 ].…”
Section: Key Features Of Adcsmentioning
confidence: 99%
“…105 DS-7300a is an ADC composed by a humanized B7-H3 IgG1 mAb and the topoisomerase I inhibitor payload DXd with a tetrapeptide-based cleavable linker (Fig 1). 106 The phase I/II first-in-human study enrolled 147 patients with tumors unselected for B7-H3 expression at doses of 4.8 mg/kg to 16.0 mg/kg once every 3 weeks (81 patients in dose escalation, 66 in 12.0 mg/kg dose expansion). 107 In the overall population, with a median of five prior treatment lines, ORR was 32% and DCR was 71.4%.…”
Section: B7-h3 (Cd276)mentioning
confidence: 99%